ДРУШТВЕНЕ ВРЕДНОСТИ КАО ОКВИР НАСЛЕДНОГ ПРАВА: ОСВРТ НА НАСЛЕДНО ПРАВО СЛОВАЧКЕ - Hamřik, Martin (Zbornik radova Pravnog fakulteta u Nišu, 2024)
The paper examines the intricate relationship between social values and inheritance law, specifically focusing on the Slovak legal system. Drawing on Thomas Hobbes's notion of law as society's collective moral compass, the paper argues that social values not only form legislation but can also be shaped and redefined by the law. The paper begins with an overview of the Slovak inheritance law, grounded in Act No. 40/1964 Coll. the Civil Code. The paper then delves into the role of social values as both limits and frameworks within which succession law operates. Five vital social values are examined in detail: liberty, family relationships, equality, responsibility, and community welfare. The paper scrutinises how these values are manifested in the Slovak inheritance law, illustrating both the alignment and tension between social values and legal norms. It explores the balance between individual liberty and familial obligations in succession, the evolving recognition of various family forms, and the implications of equality within the context of inheritance. The paper also considers the moral and legal responsibilities of heirs, both towards the deceased and towards third parties, as well as the broader societal implications of inheritance law in promoting community welfare. The analysis reveals that while the Slovak Civil Code has undergone significant amendments, it still reflects the societal norms of its time of origin, and further revisions may be necessary to align it with contemporary social values and family structures in response not only to societal shifts. The paper contributes to the understanding of the dynamic interplay between law and society within succession law, offering insights that are pertinent not only to Slovakia but also to other jurisdictions.
Keywords: друштвене вредности; наследно право; Словачка; породица; слобода; једнакост; добробит заједницe.